2015
DOI: 10.2981/wlb.00077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season on occupancy and implications for habitat modeling: the Pacific marten Martes caurina

Abstract: Season affects many characteristics of populations and, as a result, the interpretations of surveys conducted at different seasons. We explored seasonal variation in occupancy using data from four studies on the Pacific marten Martes caurina. Detection surveys were conducted during winter and summer using either cameras or track stations. We conducted a 'multiple location, paired season' analysis using data from all four study areas and a 'multiple season' analysis using seasonally replicated occupancy data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…We confirmed marten presence using both camera stations and scent detection teams in western Oregon, including in southern Oregon, and at 12 sites in the Central‐Coast of Oregon, the first such detection of martens in this area using repeatable survey methods. Estimated detection probability was similar to other studies at baited cameras in our 21‐day sampling period regardless of bait type or height (Zielinski et al ). Given both baited camera stations and scent detection teams had similar naïve false negative rates (36.4% and 33.3%), we suggest that these methods may be complimentary, reducing uncertainty in animal distribution estimates; however, we recognize that using both methods may be cost‐prohibitive for most studies.…”
Section: Discussionsupporting
confidence: 89%
“…We confirmed marten presence using both camera stations and scent detection teams in western Oregon, including in southern Oregon, and at 12 sites in the Central‐Coast of Oregon, the first such detection of martens in this area using repeatable survey methods. Estimated detection probability was similar to other studies at baited cameras in our 21‐day sampling period regardless of bait type or height (Zielinski et al ). Given both baited camera stations and scent detection teams had similar naïve false negative rates (36.4% and 33.3%), we suggest that these methods may be complimentary, reducing uncertainty in animal distribution estimates; however, we recognize that using both methods may be cost‐prohibitive for most studies.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, when examining multi‐scale habitat associations within 2 study areas in Oregon and Washington, Shirk et al () reported habitat selection did not change between seasons. In contrast, Zielinski et al () observed a strong seasonal difference in marten detections using non‐invasive survey methods; that difference may have altered interpretations of selection in that study. Moriarty et al () observed a strong difference in seasonal detections in openings when using baited track plate stations but not with telemetry, suggesting that using bait may affect seasonal differences in detection.…”
Section: Discussioncontrasting
confidence: 56%
“…We conducted this research in Lassen National Forest (LNF), California, where marten populations were monitored over 8 previous years (Fig. ; Zielinski et al ). California banned fur trapping for martens in 1954 because of the perception that habitat loss and trapping were contributing to species decline (Grinnell et al ).…”
Section: Study Areamentioning
confidence: 99%
“…Our spring–summer occupancy models contained study‐area‐specific effects, suggesting that additional variation in habitat conditions were affecting marten occupancy patterns during that season but not winter. Martens have been shown to exhibit population‐level differences in the characteristics of habitats they occur in during winter and summer, occurring in a broader range of habitat during winter when populations are at their peak and prey resources are most limited and more limited range of habitat during summer when reproduction occurs (Zielinski et al ). Despite attempting to control for variation in habitat conditions during the study design, it appears additional variation in habitat conditions is influencing density, especially for female martens, during the spring–summer.…”
Section: Discussionmentioning
confidence: 50%